2007
DOI: 10.1042/bj20060665
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde dissociates the PTP1B–E-cadherin–β-catenin complex in Caco-2 cell monolayers by a phosphorylation-dependent mechanism

Abstract: Interactions between E-cadherin, beta-catenin and PTP1B (protein tyrosine phosphatase 1B) are crucial for the organization of AJs (adherens junctions) and epithelial cell-cell adhesion. In the present study, the effect of acetaldehyde on the AJs and on the interactions between E-cadherin, beta-catenin and PTP1B was determined in Caco-2 cell monolayers. Treatment of cell monolayers with acetaldehyde induced redistribution of E-cadherin and beta-catenin from the intercellular junctions by a tyrosine phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 35 publications
10
82
0
Order By: Relevance
“…PTP1B persistently dephosphorylates ␤-catenin tyrosines, enhancing binding of ␤-catenin to cadherin (2,25). This organization of regulatory molecules is consistent with a recent report that acetaldehyde disrupted the E-cadherin-␤-catenin complex in Caco-2 cells in a process dependent on tyrosine phosphorylation (18). In this report, tyrosine phosphorylation of E-cadherin was associated with interruption of the binding of PTP1B to E-cadherin with consequent increased tyrosine phosphorylation of ␤-catenin.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…PTP1B persistently dephosphorylates ␤-catenin tyrosines, enhancing binding of ␤-catenin to cadherin (2,25). This organization of regulatory molecules is consistent with a recent report that acetaldehyde disrupted the E-cadherin-␤-catenin complex in Caco-2 cells in a process dependent on tyrosine phosphorylation (18). In this report, tyrosine phosphorylation of E-cadherin was associated with interruption of the binding of PTP1B to E-cadherin with consequent increased tyrosine phosphorylation of ␤-catenin.…”
Section: Discussionsupporting
confidence: 79%
“…The tyrosine kinase Fer and the tyrosine phosphatase PTP1B are associated directly or indirectly with the cytoplasmic domain (2,18,25). Fer is responsible for tyrosine phosphorylation of PTP1B, a state necessary for PTP1B binding to cadherin (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…Since interactions between E-cadherin, β-catenin and PTP1B are crucial for the organization of adherens junctions and epithelial cell-cell adhesion and subsequent maintenance of intestinal epithelial barrier, researchers further investigated the effect of acetaldehyde on the interactions between E-cadherin, β-catenin and PTP1B in Caco-2 cell monolayers (Sheth et al, 2007). In this study, investigators demonstrated that acetaldehyde induced disruption of interactions between E-cadherin, β-catenin and PTP1B by a phosphorylation-dependent mechanism, suggesting that this may be a mechanism whereby acetaldehyde impairs intestinal permeability.…”
Section: Role Of Acetaldehyde In Increasing Intestinal Permeabilitymentioning
confidence: 99%
“…Inhibition of PTP activity by pervanadate treatment disrupts epithelial junctions and, interestingly, impairs E-cadherin-activated Src signaling . Although some studies have reported a role for cell-contact-associated PTPs in controlling the integrity and function of epithelial junctions (Anders et al, 2006;Espejo et al, 2010;Fuchs et al, 1996;Müller et al, 1999;Sheth et al, 2007), none of the identified PTPs has been shown to control junctional SFKs.…”
Section: Introductionmentioning
confidence: 99%